Analisis Pengakuan Pendapatan Dan Beban Dalam Laporan Laba Rugi Pada PT. Monifori Nusantara - Hasibuan, David HM; Fitriantika, FIra (Institut Bisnis dan Informatika Kesatuan, 2016)
Income statement contains information about a company’s activities in a certain period more specifically its’ profits and loss, in which revenues and expenses are recognised. The research aims at analysing the recognition of revenues and expenses by a firm to compose an income statement. Analysis is conducted to discover if PT Monifori Nusantara has applied the general accounting standard. the result show that the aforementioned firm conducted a proper and accountable revenues and expenses recognition. The result also shows that electicity and depreciation expenses are not in accordance to the generally accepted accounting standard, this is because those expenses were not recognised into their own accounts.